Pengujian Optimalisasi Jaringan Kabel Fiber Optic Di Universitas Islam Indonesia Menggunakan Minimum Spanning Tree - Abrori, Muchammad; Ubaidillah, Najib (Jurnal Fourier, 2014)
Universitas Islam Indonesia (UII) intergrated campus computer network built since 1995. Development of UII integrated campus computer network is using a star topology and fiber optic (FO) cable. Considering that the star topology is the topology that requires a lot of wires, this study was conducted to determine and examine how the application of graph on the FO cable network UII integrated campus in order to minimize the cost, because FO cable network can be modeled by a graph where the buildings as points, while FO cable that connects to each building as a line. This type of research that is used here is a case study, in which data collection by observation, interviews, and documentation. This study used 4 algorithms, that is Kruskal algorithm, Prim, Boruvka and Solin algorithm to find the Minimum Spanning Tree. Based on the research that has been done, the conclution about the troubleshooting steps of optimization UII integrated campus FO cable network based graph theory has been got. From the four algorithms obtained the most optimal results FO cable length 4.700 meters long and is 1.590 meters cable lines. While the results of observations made, it is known that the existing computer network in UII integrated campus has a cable length of 6.120 meters and 2.050 meters long track. The results of the analysis showed that the resulrs of the study 23.2% more optimal than the existing computer networks in UII integrated campus.